The Bottom-Line Mentality of Leaders in Education and Training Institutions: Where to Go for Innovation? - Wan, Wenhai; Liu, Longjun; Long, Jing; Fan, Qing; Wu, Yenchun Jim (Frontiers in Psychology, 2021)
According to the social exchange theory, this study analyzed how a bottom-line mentality (BLM) among leaders affects teachers’ innovative behavior and how this relationship is mediated by relative deprivation and psychological safety and moderated by person-organization values fit. Using two stages of data collection, 491 responses from teachers were obtained and analyzed. The results revealed that leader BLM significantly negatively affected teachers’ innovative behavior, and relative deprivation and psychological safety both partially mediated this influence of leader BLM. Person-organization values fit negatively moderated the positive effect of leader BLM on teachers’ relative deprivation and the negative effect of leader BLM on teachers’ psychological safety. This study enriches the current literature about BLM and tests the influence of leader BLM on teacher’s innovation in the Chinese education and training institutions, and provides insights into favorable educational management practices.